Social Media & Celebrity Journalists' Audience Outreach in the MENA Region. Issue 2 (2nd April 2020) - Al-Rawi, Ahmed
ABSTRACT: The study attempts to understand what attracts online audiences to the social media outlets of celebrity journalists in the MENA (Middle East and North Africa) region by examining the most replied-to tweets and the most commented-on Facebook posts in order to understand what audiences find appealing and interesting. The focus of the study is related to an important part of media practice both today and in the future, and it introduces the theoretical concept of celebrity journalists 2.0 by building on the literature on personality and celebrity journalism. Using a content analysis approach and borrowing a codebook from a previous study, the top social media posts are categorized into 14 main types. The findings indicate that audiences primarily engage with celebrity journalists' posts on Twitter and Facebook that deal with self-promotion (26.6%), sharing news (26.5%), and providing opinion (20.7%). The study also shows that many journalists' top posts are limited in terms of their local and national scope, and that some journalists react to trolls in different ways.